De la sublimación del amor - Enrique Ballón Aguirre (Lexis, 2010)
The “love’s sublimation” subject was under debate in the Kant and Hegel aesthetic doctrine. This controversy was also illustrated by the colonial Hispanic-American poetry of Diego Dávalos y Figueroa, Sor Juana Inés de la Cruz and Juan del Valle y Caviedes. This article looks into the semantic structure of tree poems in order to determine their poetic scopes in the frame of the Kant-Hegel aesthetic discussion.